Switching to insulin glargine 300 U/mL: Is duration of prior basal insulin therapy important?. (August 2018) - Bonadonna, Riccardo C.; Renard, Eric; Cheng, Alice; Fritsche, Andreas; Cali, Anna; Melas-Melt, Lydie; Umpierrez, Guillermo E.
Highlights: Glycaemic control is comparable when switching basal insulin to Gla-300 or Gla-100. Lower risk of hypoglycaemia (at night or any time) with Gla-300 versus Gla-100. These outcomes are not affected by the duration of prior basal insulin therapy. Abstract: Aims: To assess the impact of duration of prior basal insulin therapy on study outcomes in people with type 2 diabetes mellitus receiving insulin glargine 300 U/mL (Gla-300) or insulin glargine 100 U/mL (Gla-100) for 6 months. Methods: A post hoc patient-level meta-analysis of data from the EDITION 1 and 2 studies. Outcomes included: HbA1c, percentage of participants with ≥1 confirmed or severe hypoglycaemic event at night (00:00-05:59 h) or any time (24 h), and body weight change. Data were analysed according to duration of prior basal insulin use: >0–≤2 years, >2–≤5 years, >5 years. Results: This meta-analysis included 1618 participants. HbA1c change from baseline to month 6 was comparable between Gla-300 and Gla-100 groups, regardless of duration of prior basal insulin therapy. The lower risk with Gla-300 versus Gla-100 of ≥1 confirmed (≤3.9 mmol/L [≤70 mg/dL]) or severe hypoglycaemic event, at night or any time (24 h), was unaffected by duration of prior basal insulin therapy. Similarly, weight change was unaffected by duration of prior basal insulin therapy. Conclusions: Switching to Gla-300 from other basal insulin therapies provided comparable glycaemic control with lower risk of hypoglycaemia versus Gla-100, regardless of duration of prior basal insulin therapy. Clinical trial registration :NCT01499082, NCT01499095 (ClinicalTrials.gov)